1-Phenylcyclohexan-1-amine hydrochloride (PCA HCl) alters mesolimbic dopamine system accompanied by neuroplastic changes: A neuropsychopharmacological evaluation in rodents. (March 2021) - Abiero, Arvie; Perez Custodio, Raly James; Botanas, Chrislean Jun; Ortiz, Darlene Mae; Sayson, Leandro Val; Kim, Mikyung; Lee, Hyun Jun; Yoon, Seolmin; Lee, Yong Sup; Cheong, Jae Hoon; Kim, Hee Jin
Abstract: The recreational use of N-methyl-D-aspartate (NMDA) antagonist phencyclidine (PCP) and ketamine have grown rapidly due to their psychotomimetic properties. These compounds induce both non-fatal and fatal adverse effects and despite the enhanced regulation, they are continuously synthesized and are being sold in the illegal drug market, including 1-phenylcyclohexan-1-amine hydrochloride (PCA). Therefore, we evaluated its abuse potential through the conditioned-place preference (CPP), self-administration, and locomotor sensitization paradigms. Pretreatment with SCH 2 3390 and haloperidol was also performed during a CPP test. We used ELISA to measure dopamine (DA) levels and western blotting to determine effects on the DA-related proteins as well as on phosphorylated CREB, deltaFosB, and brain-derived neurotrophic factor (BDNF) in the ventral tegmental area (VTA) and nucleus accumbens (NAc). Finally, we examined the effects on brain wave activity using electroencephalography (EEG). PCA induced CPP in mice and was self-administered by rats, suggesting that PCA has rewarding and reinforcing properties. PCA increased locomotor of mice on the first treatment and challenge days. SCH 23390 and haloperidol blocked the CPP. PCA altered the DA, tyrosine hydroxylase, dopamine D1 and D2 receptors as well as p-CREB and deltaFosB. Also, PCA altered the delta and gamma waves in the brain, which were then normalized by SCH 2 3390 and haloperidol. The present findings indicate that PCA may induce abuse potential through the dopaminergic system and probably accompanied with alterations in brain wave activity which is similar to that of other psychotomimetic NMDA antagonists. We advocate thorough monitoring of PCP analogs as they pose potential harm to public health. Highlights: PCA induced CPP in mice and was self-administered by rats. PCA increased locomotor in mice on the first and challenge day. SCH 2 3390 and haloperidol blocked the PCA-induced CPP. PCA altered the DA, TH, DRD1, and DRD2 as well as the p-CREB and deltaFosB. PCA altered the delta and gamma waves which were improved by SCH 2 3390 and haloperidol.